Radioactive waste processing using membranes: State of the art technology, challenges and perspectives. Issue 2 (3rd April 2022) - Pabby, A.K.; Swain, B.; Sonar, N.L.; Mittal, V.K.; Valsala, T.P.; Ramsubramanian, S.; Sathe, D.B.; Bhatt, R.B.; Pradhan, S.
ABSTRACT: Among the various separation technologies used to treat radioactive wastes, membrane technologies have been chosen in this article since they have many advantages over conventional processes. Membrane technology can be classified into different processes and, for each process, progress made till date in the radioactive decontamination of water is presented. The new directions are shown by considering advances made in membrane manufacturing and membrane processes. Thus, the combined efforts of the researchers who are engaged in membrane and membrane process design and in nuclear waste treatment were highlighted. This article focuses on applications of membrane technology in the nuclear industry and covers recent advances particularly in the field of radioactive liquid waste processing on laboratory, pilot and plant scale. Forward osmosis is highlighted for radioactive waste treatment as several recent publications pointed its potential. Some of our results Bhabha Atomic Research Centre, India) with respect to membrane-based processes are also presented.